Stimulation through CD40 and TLR-4 Is an Effective Host Directed Therapy against Mycobacterium tuberculosis - Khan, Nargis; Pahari, Susanta; Vidyarthi, Aurobind; Aqdas, Mohammad; Agrewala, Javed N. (Frontiers in Immunology, 2016)
Abstract Tuberculosis (TB) is the leading cause of morbidity and mortality among all infectious diseases. Failure of Bacillus Calmette Guerin (BCG) as a vaccine and serious side effects and toxicity due to long-term TB drug regime are the major hurdles associated with TB control. The problem is further compounded by the emergence of drug-resistance strains of Mycobacterium tuberculosis (Mtb). Consequently, it demands a serious attempt to explore safer and superior treatment approaches. Recently, an improved understanding of host-pathogen interaction has opened up new avenues for immunotherapy for treating TB. Although, dendritic cells show a profound role in generating immunity against Mtb, their immunotherapeutic potential needs to be precisely investigated in controlling TB. Here, we have devised an approach of bolstering DCs efficacy against Mtb by delivering signals through CD40 and TLR-4 molecules. We found that dendritic cells triggered through CD40 and TLR-4 showed increased secretion of IL-12, IL-6 and TNF-α. It also augmented autophagy. Interestingly, CD40 and TLR-4 stimulation along with the suboptimal dose of anti-TB drugs significantly fortified their efficacy to kill Mtb. Importantly, animals treated with the agonists of CD40 and TLR-4 boosted Th1 and Th17 immunity. Further, it amplified the pool of memory CD4 T cells as well as CD8 T cells. Furthermore, substantial reduction in the bacterial burden in the lungs was observed. Notably, this adjunct therapy employing immunomodulators and chemotherapy can reinvigorate host immunity suppressed due to drugs and Mtb. Moreover, it would strengthen the potency of drugs in curing TB.